Efektivitas Undang-Undang Perlindungan Hak Asasi Perempuan dalam Mengatasi Kekerasan Terhadap Perempuan - Destia Purwaningsih; Veny Nisratul Husna; Muhammad Ramadhan; Syahrul Mubarak; Anisa Anisa; Muhammad Audya Bintang; Muhammad Luthfi Setiarno Putera (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Violence against women remains a serious issue in Indonesia despite the existence of Law Number 23 of 2004 on the Elimination of Domestic Violence (KDRT). This study aims to evaluate the effectiveness of the implementation of this law in reducing violence against women and to identify the barriers in its implementation. The research method used is a normative legal approach, focusing on the analysis of relevant regulations and related policies. The findings show that although legal awareness has increased, many women victims of violence are still hindered by social and cultural factors in reporting the incidents. Institutional factors, such as limited resources in law enforcement agencies, also affect the effectiveness of protection. The implication of this research is the importance of a thorough evaluation of existing policies and the need to improve the capacity of law enforcement agencies to handle cases of violence against women more effectively.